Effect of high-protein fermentation amaranth feed on the functional and technological properties of milk as raw materials for cheese production - S. V. Pavlenkova (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2020)
Improving the quality of raw milk for the production of cheese in the autumn-winter period is one of the important tasks of biotechnology. It can be solved by improving the quality of feed, as they directly affect the functional and technological properties of raw milk. Amaranth silo obtained from the green mass of amaranth by canning using the developed starter culture was used in the diet of lactating cows. Scientific and economic experience was carried out on the basis of peasant farms II Korovnikov, Khokholsky district of Voronezh region. Milk was obtained from two groups of dairy cows of the Holstein-Friesian breed with an average productivity of 4200 kg of milk, selected on the basis of analogues. The diets of the experimental and control groups in accordance with the accepted experimental scheme included canned food from the green mass of amaranth and corn. Cows were fed for 105 days and evaluated the functional and technological properties of raw milk. The results of the study of the functional and technological properties of raw milk obtained from cows, in the diet of which in the autumn-winter period included high-protein canned food from amaranth, are presented. It was found that the replacement of traditional corn silage with amaranth contributed to an increase in the most important components of raw milk for cheese production: mass fraction of protein – by 0.2% (including mass fraction of casein fraction by 0.13%) and mass fraction of fat – by 0.38%. Veterinary health indicators of raw milk have also improved. In the experimental group, there was a decrease in the number of mesophilic aerobic and facultative anaerobic microorganisms (KMAFAnM) in relation to the control by 5.6%, which correlated with a decrease in the acidity of milk.